On the Performance of Sequential Half-Duplex Transmission based NOMA for Cognitive Radio Networks - P. Bachan (International Journal of Advanced Science and Technology, 2020)
Relay assisted cooperative Non-orthogonal multiple access has been one of the promising technique in 5G and beyond wireless communication networks to enhance the system performance. In this paper we study and analyze the performance of sequential half-duplex transmission (SHD) assisted NOMA for cognitive radio network. In this network a pair of half-duplex relay assisted secondary users receive and forward the message sequentially to primary user to so as to make the transmission equivalent to full-duplex transmission. Firstly, we present the mathematical analysis of probability of outage and sum rate of relay assisted cooperative user with low priority and the primary user for sequential relaying based NOMA and full duplex NOMA transmissions. Then we exhibit numerical results of probability of outage and sum rate performance of the sequential relay based NOMA system using large number of channel realizations. The simulation based numerical results confirm the applicability of mathematical analysis and exhibit the benefits of the sequential relaying assisted NOMA over full-duplex based transmissions. Keywords: Cooperative NOMA, sequential relaying (SR), outage probability and cognitive radio network.